Illuminating Bionano Interfaces: Mussel‐Glue Inspired Adhesives: A Study on the Relevance of l‐Dopa and the Function of the Sequence at Nanomaterial‐Peptide Interfaces (Adv. Mater. Interfaces 13/2019). Issue 13 (9th July 2019) - Venkatareddy, Narendra L.; Wilke, Patrick; Ernst, Natalia; Horsch, Justus; Weber, Marcus; Dallmann, Andre; Börner, Hans G.
Abstract : A tyrosinase activable adhesive peptide, inspired from mussel‐glue are identified via phage display screening. The decapeptide mimic aspects of mussel‐glue proteins, which undergo distinct structural responses at the nanomaterial interface to optimize binding kinetics and multivalent surface contacts. Solution NMR spectroscopy in combination with molecular dynamics simulation provided molecular‐level insights into the structure of the surface‐bound adhesive peptide and enabled us to understand more closely the underlying adhesion process onto the interface. More details can be found in article number1900501 by Narendra L. Venkatareddy, Andre Dallmann, Hans G. Börner, and co‐workers.